Karyotype Evolution of Talking Thorny Catfishes Anadoras (Doradidae, Astrodoradinae): A Process Mediated by Structural Rearrangements and Intense Reorganization of Repetitive DNAs - Caetano, Lucia Giuliano; Birindelli, José Luis; Simões, Fernanda Almeida; Feldberg, Eliana; Moreira Filho, Orlando; Lui, Roberto Laridondo; Venere, Paulo Cesar; Bitencourt, Jamille De A.; Lima, Moema C.C.; Viana, Patrik; Baumgärtner, Lucas; Takagui, Fábio Hiroshi (Cytogenetic and Genome Research, 2022)
Anadoras is a thorny catfish genus widespread through the Amazon and Paraguay river basins. It includes 2 nominal species, A. grypus and A. weddellii, plus Anadoras sp. "araguaia,"an undescribed species only recognized morphologically. Since Anadoras occupies a basal position within the Astrodoradinae phylogeny, it is crucial to identify its cytogenetic features to comprehend the mechanisms involved in the chromosomal diversification of this subfamily. Therefore, we performed a comparative cytogenetic analysis including all species of Anadoras. Furthermore, we applied a species delimitation analysis based on 600 bp of the mitochondrial cytochrome oxidase subunit 1 (CO1) gene to investigate the taxonomic status of the species. Cytogenetic markers revealed a high degree of similarity among Anadoras weddellii and Anadoras sp. "araguaia,"both have 2n = 56 chromosomes (24m + 10sm + 22st/a), single NOR sites on acrocentric pair 28, and 5S rDNA sites on submetacentric pair 15. A. grypus has the most divergent chromosomal characteristics because, even though it also has 2n = 56 chromosomes, it exhibits several differences in the chromosome formula, heterochromatin distribution, and number/position of the rDNA sites. In sum, we believe that the chromosome diversification of Anadoras is due to 4 mechanisms: centric fusion, pericentric/paracentric inversions, nonreciprocal translocations, and activity of transposable elements. Additionally, our phylogenetic tree revealed well-supported clades and, by barcode species delimitation analysis, confirmed the existence of 3 molecular operational taxonomic units, including the putative new species Anadoras sp. "araguaia." © 2022 S. Karger AG. All rights reserved.
Keywords: Centric fusions; Chromosome inversions